2015
DOI: 10.1007/s00246-015-1109-5
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary, Single-Institutional Experience of Surgical Versus Expectant Management of Congenital Heart Disease in Trisomy 13 and 18 Patients

Abstract: The objective of this study was to examine a large institutional experience of patients with trisomy 13 and trisomy 18 in the setting of comorbid congenital heart disease and present the outcomes of surgical versus expectant management. It is a retrospective single-institution cohort study. Institutional review board approved this study. Thirteen consecutive trisomy 18 patients and three consecutive trisomy 13 patients (sixteen patients in total) with comorbid congenital heart disease who were evaluated by our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 13 publications
1
41
0
1
Order By: Relevance
“…A Japanese study of 34 patients with T18 reported 22% two-year survival following corrective or palliative cardiac surgery, compared to 9% survival with only medical therapy [7]. Similarly, improved survival with surgical management has been reported by other small studies [8, 9]. However, these small series with relatively short postoperative follow up are not sufficient to guide healthcare providers and families regarding long term survival after CHD interventions in patients with T13 or T18.…”
mentioning
confidence: 99%
“…A Japanese study of 34 patients with T18 reported 22% two-year survival following corrective or palliative cardiac surgery, compared to 9% survival with only medical therapy [7]. Similarly, improved survival with surgical management has been reported by other small studies [8, 9]. However, these small series with relatively short postoperative follow up are not sufficient to guide healthcare providers and families regarding long term survival after CHD interventions in patients with T13 or T18.…”
mentioning
confidence: 99%
“…Two studies (Graham, Bradley, Shirali, Hills, & Atz, ; Yamagishi, ) published survival rates of infants with T‐18 after undergoing cardiac surgery, reporting 45% 2‐year survival and 86% hospital survival. One study (Costello et al, ) compared the outcomes of those infants with T‐18 who underwent cardiac surgery versus those who had palliative care and concluded that cardiac surgery should be considered for all infants with T‐18 who have moderately complex heart defects. While there are published recommendations regarding the importance of conversations between clinicians and families regarding the option of cardiac surgery (Janvier, Farlow, & Barrington, ), there is an overall lack of consensus in the literature on recommendations for corrective cardiac surgery versus palliative approaches for moderately complex heart defects (Costello et al, ; Graham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…One study (Costello et al, 2015) compared the outcomes of those infants with T-18 who underwent cardiac surgery versus those who had palliative care and concluded that cardiac surgery should be considered for all infants with T-18 who have moderately complex heart defects. While there are published recommendations regarding the importance of conversations between clinicians and families regarding the option of cardiac surgery (Janvier, Farlow, & Barrington, 2016), there is an overall lack of consensus in the literature on recommendations for corrective cardiac surgery versus palliative approaches for moderately complex heart defects (Costello et al, 2015;Graham et al, 2004). While corrective cardiac surgery may potentially help negate cardiac-related death and may improve the survival length, some argue that more data demonstrating clinical benefit of corrective cardiac surgery is needed before generalizations can be made on effectiveness (Graham, 2016;Kaneko et al, 2009;Kobayashi et al, 2010;Maeda et al, 2011;Muneuchi et al, 2011).…”
mentioning
confidence: 99%
“…Given the overall poor prognosis of babies with trisomies 18 and 13, historically these heart defects had not been surgically corrected. However, over the past 15 years, there have been a number of manuscripts published in the medical literature describing the outcomes of infants with trisomies 18 and 13 who underwent cardiac surgical repair . These reports have been accompanied by the formation and/or strengthening of advocacy and support organizations for patients and families with trisomies .…”
Section: Introductionmentioning
confidence: 99%
“…number of manuscripts published in the medical literature describing the outcomes of infants with trisomies 18 and 13 who underwent cardiac surgical repair. [4][5][6][7][8] These reports have been accompanied by the formation and/or strengthening of advocacy and support organizations for patients and families with trisomies. 9,10 These events have empowered parents of babies with trisomy 18 or 13 to initiate discussions about congenital heart surgery, sometimes contacting the offices of pediatric cardiovascular surgeons directly.…”
Section: Introductionmentioning
confidence: 99%